2009
DOI: 10.1007/s00221-009-1705-9
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal reflex responses evoked by repetitive painful stimulation delivered on the sole of the foot during late stance: site, phase, and frequency modulation

Abstract: The modulation of the lower limb nociceptive withdrawal reflex elicited during late stance by a stimulus train with frequencies of 15 and 30 Hz delivered to the mid-forefoot, arch of the foot, and heel was investigated. Stimulation was delivered at four moments of the gait cycle between heel-off and toe-off. Stimulation at 15 Hz induced larger kinematic responses at the knee and hip. Reduced plantarflexion and increased dorsiflexion, compared to control steps, were evoked at the ankle; these kinematic response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Alternatively, ankle dorsiflexion, and in particular hip and knee flexion can be achieved by eliciting the withdrawal reflex [20-22]. Electrical stimulation of the sole of the foot has been shown to be effective to elicit the nociceptive withdrawal reflex (NWR) in the lower limb of healthy and hemiparetic individuals; the muscle and kinematic NWR responses were gait phase, stimulation site, frequency, and intensity dependent [23-26]. The characteristic kinematic response in hemiparetic individuals included dorsiflexion of the ankle joint and flexion of the knee and hip joints [25].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, ankle dorsiflexion, and in particular hip and knee flexion can be achieved by eliciting the withdrawal reflex [20-22]. Electrical stimulation of the sole of the foot has been shown to be effective to elicit the nociceptive withdrawal reflex (NWR) in the lower limb of healthy and hemiparetic individuals; the muscle and kinematic NWR responses were gait phase, stimulation site, frequency, and intensity dependent [23-26]. The characteristic kinematic response in hemiparetic individuals included dorsiflexion of the ankle joint and flexion of the knee and hip joints [25].…”
Section: Introductionmentioning
confidence: 99%
“…Central, non-linear summation of afferent non-nociceptive input occurs within the spinal reflex circuits after stroke. Summation has previously been demonstrated for nociceptive input in healthy volunteers during gait [3] and arm and leg cycling [2] and with the present study sensory integration for nonnociceptive intensities has been demonstrated also after damage to the nervous system. This observation has implications for the use of tactile cutaneous stimulation as a therapeutic modality for gait rehabilitation after stroke.…”
Section: Discussionmentioning
confidence: 74%
“…Sensory input from the arms and legs support functional movements, however the input is modulated by the phase of the legs in the cyclic movement. Integration of nociceptive [2] and tactile [3] afferent activity in spinal reflex pathways has resulted in enhanced reflexes during gait. Moreover, according to the flexor reflex afferent theory multisensory integration is occurring in the spinal reflex pathways which include tactile cutaneous afferents [4].…”
Section: Introductionmentioning
confidence: 99%
“…In general terms, ankle flexors muscles (primarily tibialis anterior) are activated after stimulation of the medial and distal regions of the sole of the foot, while ankle extensor muscles (mainly soleus and gastrocnemius medialis) are activated after stimulation of the proximal region of the sole of the foot (Andersen, 2007). However, these studies did not investigate in detail the effects of the spatial resolution of stimulated area, and consequently a fixed number of locations (ranging from three to sixteen) is chosen and non-uniformly distributed across the sole of the foot Andersen et al, 2004;Emborg et al, 2009;Spaich et al, 2009).…”
Section: Stimulation Sitesmentioning
confidence: 99%